The crisis of the thirties. The Poles: out! - Frey, Yves (Polonia Inter Gentes, 2023)
The economic crisis began in France in the second half of 1930. It reached its peak in 1934 and 1935 and resulted in a very high unemployment rate. To cope with these difficulties, the French government decided to protect French workers by limiting the number of foreign workers. The Poles had to return to their country under increasingly restrictive conditions. Woe betide strikers, union members and communists. The number of Poles fell by 17% between 1931 and 1936. After the respite provided by the Front Populaire, which was more concerned about foreign workers, the Poles lived in fear of having to leave France. The most politically committed joined the International Brigades during the Spanish Civil War.